Antioxidant and Photoprotective Effects of Blanch Water, a Byproduct of the Almond Processing Industry - Francesco Paolo Bonina; Antonio Tomaino; Domenico Trombetta; Luisa Rizza; Teresita Arcoraci; Carlo Bisignano; Maria Martorana; Giuseppina Mandalari (Molecules, 2013)
The aim of the present work was to evaluate the antioxidant and photoprotective effect of blanch water (BW), a byproduct of the almond processing industry. The polyphenolic content of a BW extract, the level of proanthocyanidins and the vanillin index determination were determined. The antioxidant activity and the radical scavenging activity of the BW were evaluated by a range of in vitro tests. The in vivo photoprotective effect was investigated using a formulation containing 2% of the BW extract on skin erythema induced by acute UV-B exposure in twelve volunteers. Results confirmed the presence of added-value antioxidant compounds in the industrial BW extract, and the most representative compounds were naringenin-7-O-glucoside and kaempferol-7-O-rutinoside. The proanthocyanidin content was 71.84 ± 5.21 cyanidin equivalents/g of BW extract. The good antiradical activity of the BW extract was demonstrated in both the DPPH• test and in the Reducing Power test. The percentage inhibition of erythema obtained using a formulation of BW was 50.48, value clearly demonstrating an effect against photooxidative damage in vivo.